2022
DOI: 10.22201/fmvz.24486760e.2022.1046
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different inorganic selenium levels in laying quails (Coturnix coturnix Japonica) diets on performance, egg quality, and serum biochemical parameters

Abstract: Inorganic selenium supplementation in poultry diet has been controversial. It has been linked that the excess and deficiency of this mineral can lead to health problems in these animals. However, this fact is not so evident in quails. In this research 120 female quails (220.6 ± 8.2 g) at 10 weeks of age were allocated to five treatment groups with six replicates of four quails in each. Experimental diets were formed by adding 0, 0.25, 0.50, 0.75 or1.00 mg/kg of inorganic selenium (sodium-selenite) to the diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The nutrition of avian species plays a key role in their health, egg quality, and body growth [ 1 , 2 ]. In poultry production, adequate nutrient intake is crucial for optimal performance [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…The nutrition of avian species plays a key role in their health, egg quality, and body growth [ 1 , 2 ]. In poultry production, adequate nutrient intake is crucial for optimal performance [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moisture, protein, lipids, ash, and Se concentration (Table 3) were not affected by the interaction (p > 0.05) between SO and SeY levels. Sarmiento-García et al [16] reported that supplementation of laying quail diets with sodium selenite up to 1 ppm for 20 weeks had no effect on production performance, meat composition, or serum biochemical parameters. High SO in diets decreased the moisture and increased Se concentration in the meat of quails.…”
Section: Meat Quality and Compositionmentioning
confidence: 99%
“…[15] Quail performance can be improved by selenite reserves in muscles that support antioxidant defenses. [16] In addition, Se is a component of the enzyme glutathione peroxidase, which is a selenoenzyme responsible for fighting free radicals in muscle tissue, preventing oxidative damage by acting as a modulator of the immune system and reproductive system. [17] There are many studies in the literature which have tested Se addition in quails' diets to improve the oxidative stability of the meat, however the antioxidant role of Se is still unclear [12,15] and the effects of organic or inorganic Se as dietary supplementation on its final concentration in quail meat and on the meat quality are not conclusive.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations